Frame of reference managing e-health programs - Serrano Santoyo, Arturo; Rojas Mendizabal, Veronica A; Castillo Olea, Cristian (Ingeniería Solidaria, 2017)
Introduction: This article derives from the research “Innovation, complexity, and management in socio-technical systems”. It was conducted between 2014 and 2017 at the Center for Scientific Research and Higher Education of Ensenada, Baja California, Mexico. The systems for processing, distributing, and transporting digital information currently have a great impact on the operation of the healthcare industry, creating opportunities to improve its services and coverage and seeking to streamline health information processes of an administrative, clinical and operational nature. A perspective of electronic health or digital health (e-health) from the science of complexity can extract new findings towards the understanding of the e-health ecosystem at the local, regional and national levels, increasing its effectiveness as a potential enabler of social welfare. Methodology: This article turns to the science of complexity as a methodological basis to develop a frame of reference, considering the interactions between agents of the ecosystem and the characteristics of the context where e-health programs and interventions will be implemented. Results: A frame of reference is presented to address e-health programs, projects and interventions from a comprehensive perspective taking into account the role played by the interactions between predominant agents of the system and the characteristics of the context that will be intervened. As an example of application of the proposed frame of reference, the project “Tele-epidemiology of vector-borne diseases” being carried out by our research group is briefly described. Conclusions: The proposed frame of reference provides a platform for analysis and management that seeks to take advantage of the potential of e-health to become an effective vehicle for solidarity and social development.